2023
DOI: 10.3390/polym15143133
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Comparison of PLA-PEG-PLA and PEG-PLA-PEG Copolymers for Curcumin Delivery to Cancer Cells

Neda Rostami,
Farzaneh Faridghiasi,
Aida Ghebleh
et al.

Abstract: Curcumin (CUR) has potent anticancer activities, and its bioformulations, including biodegradable polymers, are increasingly able to improve CUR’s solubility, stability, and delivery to cancer cells. In this study, copolymers comprising poly (L-lactide)-poly (ethylene glycol)-poly (L-lactide) (PLA-PEG-PLA) and poly (ethylene glycol)-poly (L-lactide)-poly (ethylene glycol) (PEG-PLA-PEG) were designed and synthesized to assess and compare their CUR-delivery capacity and inhibitory potency on MCF-7 breast cancer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Then, it was completely washed in distilled water. To examine the stability of the emulsions, the fresh Pickering emulsion (5.0 mL) and hydrogel (2.0 g) were packed into a dialysis bag with a 14 kDa cutoff (Rostami et al., 2023 ; Shahbazizadeh et al., 2022 ). Then, it was immersed in 200 mL of gastric juice, under magnetic stirring at 100 rpm and consequently transferred to intestinal release medium on a magnetic stirrer (150 rpm) at a constant temperature (37°C) (Shahbazizadeh et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Then, it was completely washed in distilled water. To examine the stability of the emulsions, the fresh Pickering emulsion (5.0 mL) and hydrogel (2.0 g) were packed into a dialysis bag with a 14 kDa cutoff (Rostami et al., 2023 ; Shahbazizadeh et al., 2022 ). Then, it was immersed in 200 mL of gastric juice, under magnetic stirring at 100 rpm and consequently transferred to intestinal release medium on a magnetic stirrer (150 rpm) at a constant temperature (37°C) (Shahbazizadeh et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The above results fully demonstrated that the modified pH-sensitive PLA microspheres could improve the anticancer effect. Neda Rostami et al 21 synthesized (PLA–PEG–PLA) and (PEG–PLA–PEG) and showed by molecular dynamics simulations and free energy analysis that PLA–PEG–PLA has a higher tendency to interact with the cell membrane and more negative free energy, indicating that PLA–PEG–PLA is a better carrier for cell membrane penetration. Furthermore, PLA–PEG–PLA exhibited higher drug loading and more controlled release rates, leading to greater cell death in MCF-7 breast cancer cells, probably because of the stronger hydrophobicity of PLA–PEG–PLA than PEG–PLA–PEG.…”
Section: Biodegradable Carrier Materials For Microsphere Injectionsmentioning
confidence: 99%